The Impossible Stability? The Italian Lower House Parliamentary Elite After a “Decade of Crises” - Verzichelli, Luca; Marino, Bruno; Marangoni, Francesco; Russo, Federico (Frontiers in Political Science, 2022)
The article explores recent changes in the Italian Lower House parliamentary elite thanks to a novel set of data on Italian MPs, including information on the Italian Lower House between 1946 and 2018. After a first discussion on some crucial long-term trends of Italian Lower House MPs (their turnover rate, seniority, gender balance, party-related or institutional experience), we focus on some possible explanations of the profound transformation that occurred in the past decade. In particular, during the so-called decade of the crises, between the early and the late 2010s, two critical general elections (in 2013 and 2018) would have brought about not just a dramatic rate of parliamentary turnover but even a new mix of important characteristics among Italian MPs. Subsequently, we point at three MP categories, taken as the most relevant proxies of the innovations in the Italian parliamentary elite. These categories are based on the length of MPs’ parliamentary career, their previous party or institutional experience, and their gender. We discuss the changes in the numerosity of these categories vis-à-vis the entire Lower House from the mid-1940s or early 1950s up to the late 2010s. Moreover, we also tackle the parliamentary career and some features related to the return to Parliament of MPs belonging to these three categories. Two implications emerge from our analysis. First, the changes of the decade of the crises are critical, since the increase in the parliamentary representation of amateurs and also female and young citizens cannot be compared to any other conjuncture of the Italian republican age. Moreover, such changes cannot just be attributed to the – still influential – presence of a populist and innovative parliamentary actor like the Five Star Movement. Second, despite such changes, the perspectives of parliamentary career and parliamentary survival remain very much subordinated to belonging to specific parliamentary party groups. This signals that, despite broad discussions about the positive role exerted by new political actors and the demand for a stronger descriptive representation, what seems to matter in the Italian Lower House is belonging to more or less numerous and powerful parliamentary party groups.